Formulation And Test Effectiveness Of Antifungal Cream Of Mugwort Ethanol Extract (Artemisia vulgaris L) On Candida Albicans ATCC 10231 - Yaya Sulthon Aziz; Naila Matsna Assyifa; Amalia Rahma Pratiwi; Siska Tri Wahyuni (Universitas Airlangga, 2024)
According to the people of the Tengger Tribe for generations, a Mugwort plant (Artemisia vulgaris L.) was believed to be useful as a treatment for fungal infections. Based on research reports, the Mugwort plant (Artemisia vulgaris L.) contained bioactive compounds such as flavonoids, tannins, saponins, steroids, and alkaloids. These active compounds had activity as an antifungal. This study aimed to formulate, evaluate, and test the activity of a cream preparation with type m/a ethanol extract of Mugwort (Artemisia vulgaris L.) in inhibiting the growth of the fungus Candida albicans ATCC 10231. This type of research was laboratory experimental research. Samples were taken by simple random sampling to test the inhibition of Candida albicans ATCC 10231. The results of the physical quality test of Mugwort leaf extract (Artemisia vulgaris L.) cream from the 4 formulation with test parameters including organoleptic, pH, spreadability, adhesion, and viscosity test, were in accordance with the established quality standards. The results of the physical evaluation of the antifungal cream showed organoleptic properties, homogeneity, pH 6, spreadability test F1 5.2, FII 5.1, FIII 5.3, and FIV 5.4 cm, FI adhesion test 5.3, FII 5.3, FIII 5.4, and FIV 5.5 seconds. Meanwhile, in the viscosity test the results were FI 24,606, FII 30,836, FIII 40,198 cP, and FIV 38,695 cP. The inhibition test results were analyzed by calculating the average for each concentration, performed three times. The results showed that the ethanol extract of Mugwort leaf (Artemisia vulgaris L.) cream had antifungal effectiveness with an average value of 8.6 mm at a concentration of 2.5% (moderate category), 10.3 mm at a concentration of 5% (medium category), 11 mm at a concentration of 10% (strong category) and 12 mm at a concentration of 20% (strong category). The study concluded that the ethanol extract of Mugwort Leaf (Artemisia vulgaris L.) cream was effective in inhibiting the growth of Candida albicans ATCC 10231. Keywords: Mugwort (Artemisisa Vulgaris L), Antifungal, Candida Albicans ATCC 10231